A arte de contar histórias como ferramenta na formação de leitores na Biblioteca Pública Infantil de Sergipe : projetos implantados de 2007 a 2018 - Stocker, Claudia Teresinha (2019)
The purpose of this paper is to show that a study on Storytelling as a tool for the training of readers in public libraries, specifically in Children's Libraries, aimed to show that permissive and well-coordinated actions can contribute to the constant use of public libraries, which are seen until today, by the majority of the society, like deposit of old books. But the reality of the public library of the 21st century goes against the old labels. The library today can be seen as a cultural hub serving the community in which it is embedded. To bring to the pages of this study the making of the Children's Public Library of Sergipe from 2007 to 2018, is to leave the historical record of a period where the library was most evident, becoming a reference in the State and abroad. Under the management of a professional librarian and with the implementation of permitting projects to encourage reading, the children's library showed that the Public Library space can contribute to the development of the creative and critical potential of children, teachers, employees and the people wo was going to that space. Storytelling and reading mediation are transformative activities that awaken in the adult and children, the taste for literature and the permanent contact with books.